Analisis Program Edupreneur Berbasis Kearifan Lokal (Studi Kasus di Sekolah Dasar Muhammadiyah 1 Menganti Gresik) - Nur Rahmawati; Mulyadi; Muhammad Indra Adi Gunawan (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2022)
This research was motivated by the existence of a local wisdom-based edupreneur program at the Muhammadiyah 1 Menganti Gresik Elementary School. The aim of this research is to determine and describe the implementation of the local wisdom-based edupreneur program implemented at the Muhammadiyah 1 Menganti Gresik Elementary School. This type of research is case study research which is descriptive qualitative in nature. The research subjects were the principal, head of curriculum, head of student affairs, class teachers and students. The local wisdom-based edupreneur program is the object of this research. The methods used to collect data are interviews, observation and documentation. Next, data analysis refers to Miles and Huberman through data reduction, data presentation, and data verification. The research results show that the local wisdom-based edupreneur program at Muhammadiyah 1 Menganti Gresik Elementary School began to be implemented around 2014 when this school still had three classes, namely first, second and third grades. Entrepreneur day activities are held once a month and are held on Friday in the last week, this activity is carried out in rotation starting from class VI to class I. This activity is intended to develop the entrepreneurial spirit of students. Meanwhile, the implementation of Entrepreneur Day at the Muhammadiyah 1 Menganti Gresik Elementary School is based on local wisdom, namely by selling various types of traditional food and types of food that have become icons where the school was founded, because the school is located in Sidowungu village which is famous as a chicken sales center so that the edupreneur program is held in Muhammadiyah 1 Menganti Gresik Elementary School uses chicken as the basic ingredient.